Huddes Specilla circularia (1656), vertaald in het Nederlands - Davidse, Ad; Hudde, Johannes (Studium, 2018)
This small treatise by Hudde discusses “circular lenses, or how one can construct all kinds of optical instruments by circular figures only, both microscopes and telescopes, so that they produce the same effect as elliptical or hyperbolic figures, or at least as close as possible”.